HUBUNGAN PENGETAHUAN IBU TENTANG SANITASI MAKANAN DENGAN KEJADIAN DIARE PADA BALITA - astuti, wiwin puji; herniyatun, -; yudha, hendry tamara (LPPM STIKES MUHAMMADIYAH GOMBONG, 2011)
Diarrhe is a serious public health problem because the mortality rate due to diarrhea is still high, especially in Balita (Children under five age). Knowledge of food sanitation is used as a basis and efforts aimed at hygiene and food safety in order not to cause toxicity and human disease, especially about the diarrhea. The aim of this study is to find out correlation between mothers knowledge about food sanitation with diarrhea case occurance of Balita in Klirong I Community Health Center work area. The type of the research is case control with retrospective approach. Population in this study were mothers who have children who ever had treatment Klirong I Community Health Center. The samples were taken by purposive sampling technique. There were 68 respondents used as the samples that devided as cases population (34 respondents of Balitas who suffered diarrhea) and control population (34 respondents ofÂ Balitas who never suffered from diarrhea). The data were analysed by using chi square test. chi square test. showed that x test =7.074 > 5.991 from the x table. It means that there is a correlation betwen motherâ€™s knowledge about food sanitation with diarrhea case occurance in Balita. Sanitation knowledge can influence the diarrhea occurance. Keywords. Diarrhea, toddler/Balita, food sanitation